Application of the Predictive deconvolution on a seismic line Al-Najaf and Al-Muthanna Governorates in Southern Iraq - Ali, Kamal K.; Khaleefah, Laith R. (Iraqi Journal of Science, 2018)
This study deals with the processing of field seismic data for a seismic line located within the administrative boundaries of Najaf and Muthanna governorates in southern Iraq (7Gn 21) with a length of 54 km. The study was conducted within the Processing Department of the Oil Exploration Company using the Omega system, which contains a large number of programs that deal with processing, through the use of these programs applied predictive deconvolution of both( gap) and (spike). The final section was produced for both types. The gap predictive deconvolution gave improvement in the shallow reflectors while in deep reflectors it did not give a good improvement, thus giving a good continuity of the reflectors at the expense of resolution, whereas spike predictive deconvolution caused an increase in frequency noise in seismic sections, giving a good resolution at the expense of continuity.